ANALISIS ALIRAN FILSAFAT PADA KURIKULUM MERDEKA - Yunia Nurholishoh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to analyze the integration of philosophical streams, namely progressivism, humanism, constructivism, behavioral elements, and realism, within the Merdeka Curriculum. The research methodology employed is qualitative-descriptive with a secondary analysis approach, drawing data from relevant studies. The findings reveal that the Merdeka Curriculum judiciously incorporates the principles of progressivism, humanism, and constructivism into its teaching structure. Although not explicitly adopting a behaviorist approach, elements are reflected in the use of rewards and reinforcement as motivators for students. The integration of realism provides a robust epistemological foundation, ensuring an objective understanding of the world around the learners. Data analysis involves evaluating the positive impact of progressivism, humanism, constructivism, behaviorism, and realism on students' motivation, achievements, character, and understanding. These findings affirm the success of the Merdeka Curriculum in creating a holistic learning environment that fosters both academic intelligence and character development. This research contributes to a profound understanding of the implementation of philosophical streams within the Merdeka Curriculum, with the hope of continuously improving and optimizing educational approaches to nurture a comprehensive and globally-ready generation. Key Word: Merdeka Curiculum, Integration of philosophical Streams, Holistic Education